TREATMENT OUTCOMES OF DIABETIC KETOACIDOSIS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AT CAN THO CENTRAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the treatment outcomes of diabetic ketoacidosis in patients with type 2 diabetes mellitus.Subjects and methods: A case series study was conducted on 30 patients diagnosed with diabetic ketoacidosis due to type 2 diabetes mellitus who were hospitalized at Can Tho Central General Hospital from 12/2024 to 3/2026.Results: The mean age was 59.13 years, and females accounted for 70% of the study population. A normal body mass index was observed in 43.3% of patients, while 46.7% had a diabetes duration of 5-10 years. The most common complications were acute kidney injury (80%) and hypokalemia (73.3%), and no mortality was reported. The duration of fluid therapy differed significantly between the two levels of acidosis severity (p = 0.049).Conclusion: The time to resolution of acidosis, duration of Insulin infusion, and length of hospital stay did not differ according to the severity of diabetic ketoacidosis. However, the duration of fluid therapy was associated with the degree of ketone reduction. Acute kidney injury and hypokalemia were the two most common complications.
Keywords: Type 2 diabetes mellitus, diabetic ketoacidosis, DKA.